LEVEL OF KNOWLEDGE AND COMPLIANCE WITH PERSONAL PROTECTIVE EQUIPMENT USE IN HEALTHCARE WORKERS - Reza Fajrinmuha; Nuraini Wulandiana; Ratna Dwi Wulandari; Nyoman Anita Damayanti; Armunanto Armunanto (Jurnal Berkala Epidemiologi, 2022)
Background: The effort to control and prevent COVID-19 in health facilities is to optimize the use of Personal Protective Equipment (PPE) according to guidelines set by the government. The compliance of healthcare workers using the specified PPE will affect the control and prevention of the COVID-19 pandemic. Purpose: The study aims to measure the prevalence of COVID-19 in healthcare workers and to find out an overview of knowledge level and compliance with the use of PPE among healthcare workers in East Java Province during the COVID-19 pandemic. Methods: This research was an observational study with a descriptive cross-sectional design. The study population was around 183,501 healthcare workers in East Java Province, with criteria of healthcare workers who worked during the COVID-19 pandemic and were willing to be respondents. This study used a probability sampling method with a simple random sampling technique consisting of 129 healthcare workers. The variables used were knowledge level, compliance with the use of PPE, and the history of COVID-19 infection. Primary data have collected by an online questionnaire platform from September 3rd, 2020 to September 12th, 2020. Results: The prevalence of COVID-19 among healthcare workers in East Java was 6.20%, and all the healthcare workers infected with COVID-19 have a good level of knowledge and compliance with the use of PPE in health facilities. Conclusion: Most healthcare workers have good knowledge and compliance with using PPE.